EFEKTIVITAS UPAYA PENANGANAN STUNTING MENGGUNAKAN DANA DESA DI DESA MEKARWANGI KECAMATAN TAROGONG KALER KABUPATEN GARUT - Aryanto, Attayya Kaysa; Irawati, Ira (Jurnal Progress Administrasi Publik, 2024)
Through Presidential Regulation Number 72 of 2021 on Accelerating Stunting Reduction and Minister of Village, Development of Disadvantaged Regions, and Transmigration Regulation Number 8 of 2022 on Priority Use of Village Funds for the Year 2023, the central government mandates all levels of governance to prioritize addressing stunting in the implementation of development and organized governance. The Village Government of Mekarwangi implements this policy by utilizing Village Funds as a funding source for the Supplementary Feeding Program. However, in its implementation, the program has not fully operated effectively due to deficiencies in the program's structure and the implementation process. This study aims to elucidate the effectiveness of mitigation efforts utilizing Village Funds in Mekarwangi Village. The theoretical foundation for this research is Riant Nugroho's Effectiveness Theory. The research adopts a descriptive qualitative research method with primary data obtained through observation and interviews, supplemented by secondary data from document and literature studies. Data analysis involves data condensation, data presentation, concluding statements, and verification. The findings indicate that the mitigation efforts utilizing Village Funds in Mekarwangi Village are still not entirely effective, particularly in the principles of the program, targets, and environment, necessitating a reassessment of the program's structure, target beneficiaries, and awareness campaigns about stunting.   Keywords: Effectiveness; Program; Stunting; Village.